The Influence of Group Counseling with a Rational Emotive Behavioral Therapy (REBT) Approach on Enhancing Students' Learning Motivation - Dinayanti Dinayanti; Nurussakinah Daulay (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2024)
A research team at SMP Negeri 17 Medan began observing the desire of ninth-grade students to learn using the Rational Emotive Behavior Therapy (REBT) method. Students from classes IX-A and IX-B, representing a total population of 25, with 8 samples taken from each class, were selected as the sample for this quantitative research study, which employed a Nonequivalent Control Group Design. Tests were used as the instrument in this investigation. Both descriptive and inferential statistics were used to analyze the data. The ninth-grade students at SMP Negeri 17 Medan demonstrated a significant increase in their enthusiasm for learning after receiving Rational Emotive Behavior Therapy (REBT). This is evidenced by the fact that the average learning motivation scores increased after the implementation of the REBT method. Furthermore, the hypothesis test results reinforced these findings by showing that the experimental group had a much higher level of learning motivation compared to the two control groups. Therefore, it is safe to say that REBT was effective. It made students more motivated to learn, more confident, more enthusiastic about tackling difficult tasks, and ultimately more resilient. This indicates that the REBT approach could be a potentially effective strategy for improving the quality of learning and academic achievement of students in the school environment.